2006
DOI: 10.1002/cncr.22419
|View full text |Cite
|
Sign up to set email alerts
|

Use of p63 for distinction of glandular versus squamous lesions in cervicovaginal specimens

Abstract: Perinatal hypoxic‐ischemic encephalopathy (HIE) is a significant cause of mortality and morbidity in infants and young children. Therapeutic opportunities are very limited for neonatal and pediatric HIE. Specific neural systems and populations of cells are selectively vulnerable in HIE; however, the mechanisms of degeneration are unresolved. These mechanisms involve oxidative stress, excitotoxicity, inflammation, and the activation of several different cell death pathways. Decades ago the structural and mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The antibody can also detect isolated small HSIL cells and can improve the sensitivity of detecting these 'litigation' cells that are potentially easy to be missed. P63 has been suggested to be useful to distinguish squamous and glandular lesions in cervical samples 39 and the endocervical glandular cells in this study was found to be negative for p634A4. In the squamous mucosa, p63 expression is often localized to the basal and parabasal cells of mature or metaplastic stratified squamous epithelium but may be present in all cell layers in atrophic epithelium.…”
Section: P63 and Cervical Epithelial Differentiation And Carcinogenesissupporting
confidence: 52%
“…The antibody can also detect isolated small HSIL cells and can improve the sensitivity of detecting these 'litigation' cells that are potentially easy to be missed. P63 has been suggested to be useful to distinguish squamous and glandular lesions in cervical samples 39 and the endocervical glandular cells in this study was found to be negative for p634A4. In the squamous mucosa, p63 expression is often localized to the basal and parabasal cells of mature or metaplastic stratified squamous epithelium but may be present in all cell layers in atrophic epithelium.…”
Section: P63 and Cervical Epithelial Differentiation And Carcinogenesissupporting
confidence: 52%
“…This antibody is not expressed in AGC, adenocarcinoma, or normal glandular cells. p63 stains basal cells and may be a diagnostic pitfall in atrophic Pap tests 118…”
Section: P63mentioning
confidence: 99%